(untitled) (Experimental biology, 2015)
The gray rat (rattus norvegicus) is a typical synanthropic rodent, one of the most undesirable and dangerous neighbor of a human being. Rattus norvegicus is a bearer of a quite number of dangerous infections for people and animals, such as plague tularemia, leptospirosis, listeriosiss, salmonellesis, rabies, pseudotuberculosis etc. The analysis of infections of common rat was put into practise in two large cities of Kyrgyzstan and Kazakhstan.There is data (information) of contamination of the grey rat of many years in Bishkek and Almaty. In these cities at The Kazakh Scientific Center of quarantinable and zoonotic infections n. M. Aikimbaev, Almaty c. and The Kyrgyz Repulic Center of quarantinable and extremely dangerous infections, Bishkek c. researches were done by bacteriological,biological and serological methods for the purpose of establishment the grey rats’ bearer of zoonotic infections.In Bishkek was registered a tendency of a number growth of ill rats in 2003-2012 in comparison with 1990-ths years.In 2001-2005 y. in Almaty c. brucellosis and leptospirosis earlier shoving absence were revealed, in 2012 due to the zoonotics number decrease, increased contamination of the grey rats by particular diseases.